Kontribusi Filsafat Ilmu dalam Studi Ilmu Agama Islam: Telaah Pendekatan Fenomenologi - Mulyadi Mulyadi (Ulumuna, 2010)
Islamic studies is considered both religious and scientific activities. As scientific activities it needs to establish its scientific bases through the study of philosophy of science. From the perspective of philosophy of science, almost all types of knowledge experience what is called a shifting of paradigm. Islamic studies is not exception, so that changes, re-formulations, and improvement of its epistemological design and construction are very possible. Thus, Islamic studies are not static, but dynamic. It always faces current challenges of changing times and styles that are always experienced by Muslims and human being in general. This means that Islamic studies that used to apply purely normative and empirical approaches to phenomena of human religiosity should shift to phenomenological one. The approach is worth to broaden insights and open new horizons in search for the essence and the fundamental structure of human religiousity.